Philippine Computing Journal (Philippines : Computing Society of the Philippines, 2015)
u
u
u
u
u
On Self-Reducibility and Reoptimization of Closest Substring Problem -- Homogeneous and other Weight Functions -- Graph an Information Theoretic Analysis of Correlation between Stock Market Indices -- A System for Sensing Human Sentiments to Augment a Model for Predicting Rare Lake Events -- Multi-Campus Implementation of University Information Systems.
Includes bibliographical references.